Numerical-experimental analysis of a carbon-phenolic composite via plasma jet ablation test - Silva Pesci, Pedro Guilherme [UNESP]; Machado, Humberto Araujo; Paula e Silva, Homero de; Paterniani Rita, Cristian Cley; Petraconi Filho, Gilberto; Botelho, Edson Cocchieri [UNESP] (Iop Publishing Ltd, 2018)
Materials used in space vehicles components are subjected to thermally aggressive environments when exposed to atmospheric reentry. In order to protect the payload and the vehicle itself, ablative composites are employed as TPS (Thermal Protection System). The development of TPS materials generally go through phases of obtaining, atmospheric reentry tests and comparison with a mathematical model. The state of the art presents some reentry tests in a subsonic or supersonic arc-jet facility, and a complex type of mathematical model, which normally requires large computational cost. This work presents a reliable method for estimate the performance of ablative composites, combining empirical and experimental data. Tests of composite materials used in thermal protection systems through exposure to a plasma jet are performed, where the heat fluxes emulate those present in atmospheric reentry of space vehicles components. The carbon/phenolic material samples have been performed in the hypersonic plasma tunnel of Plasma and Process Laboratory, available in Aeronautics Institute of Technology (ITA), by a plasma torch with a 50 kW DC power source. The plasma tunnel parameters were optimized to reproduce the conditions close to the critical re-entry point of the space vehicles payloads developed by the Aeronautics and Space Institute (IAE). The specimens in study were developed and manufactured in Brazil. Mass loss and specific mass loss rates of the samples and the back surface temperatures, as a function of the exposure time to the thermal flow, were determined. A computational simulation based in a two-front ablation model was performed, in order to compare the tests and the simulation results. The results allowed to estimate the ablative behavior of the tested material and to validate the theoretical model used in the computational simulation for its use in geometries close to the thermal protection systems used in the Brazilian space and suborbital vehicles.
Keywords: ablation; plasma; ablative composites; thermal protection systems; reentry